The Standard Estimation of Production Cost of Almond Rain-Fed Varaietes in Homs Governorate - almnsour, rana; Idris, Khitam; Al-Ali, Jamal (Jordan Journal of Agricultural Sciences, 2023)
The objective of this research is to study the standard estimation production cost of almond rain-fed varirties in Homs Governorate for 2019. The order to achieve its objectives, the research depends on econometric and statistical analysis conducted on the primary data collected through a face-to-face interview with the farmers in the eastern district of Homs province. The results indicated that in the almond varieties cultivated for green consumption (Auja - Dfadaei), the Auja variety had the highest productivity compared to Dfadaei, while the dry varieties, the French variety had the highest productivity compared with the rest of the cultivated varieties in the studied area, where its productivity reached (164.7) kg. / dunums, while the lowest productivity was for the albladi variety, which amounted to (104.48) kg/dunam. The results of the descriptive analysis of the structure of production costs showed that the highest value of the total costs was for the French variety and the lowest for the albaldi variety In terms of the profit achieved, the French variety ranked first, as it was found that the use of one Syrian pound of the changing assets of the French variety led to a profit of (3.38) SP. as for estimating the total cost function, it was the cube model was the most suitable for the relationship adopted in the study, through its estimation in the short term, it was found that the present productivity scale of all verities is away from the productivity scales for economic efficiency and maximizing profit. And the optimal output size in the long run was (23.71) tons this output level requires an optimal area of (42) donums, and the minimum price at which almond growers sell (249100.17) SP/ton was calculated. The long-term supply function was derived, and it was found that there is a positive relationship between the quantity supplied of almonds and the price, when the price is greater than (249100.17) SP/ton. It was found, through measuring technical efficiency that about (28%) of economic resources were not exploited optimally.